Traces of Islamic Civilization in Sustainable Development: An Ecosocial History Perspective of the Islamic World - Yulia, Devi; Hanipah; Cahyati, Ananda Tri; Muarif, Muhamad Ari; Ridwan, Mohammad (Sekolah Tinggi Agama Islam Kuningan, 2025)
The current discourse on sustainable development is often dominated by the technocratic and secular Western paradigm, while the historical contributions of non-Western civilizations, especially Islam, have received less academic attention. This article aims to explore the values and historical practices in classical Islamic civilization that reflect the principles of sustainable development, emphasizing the ecosocial dimension of history as the main analytical approach. The method used is qualitative research with a historical-thematic approach, through a literature study of primary and secondary sources from three major Islamic civilization cities: Baghdad, Córdoba, and Timbuktu. The analytical techniques used include data reduction, thematic categorization, and hermeneutic interpretation of texts and social-ecological practices. The results show that classical Islamic civilization has applied the principles of social justice, ecological balance, and spiritual responsibility in urban governance, agricultural systems, water management, and social institutions such as waqf. The intellectual contributions of Muslim figures in the fields of science, agriculture, and architecture also laid the foundation for a holistic development framework. This research confirms that maqāṣid al-sharī'ah values have high relevance to the Sustainable Development Goals (SDGs) and can be an alternative to today's development paradigm that is more ethical and contextual. The findings are expected to enrich the development discourse with a history- and value-based Islamic perspective.